FILSAFAT EKONOMI ADAM SMITB - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This essay wants to describe and analyze Admn Smith's philosophy of Economic. Adam Smith, as the Father of Economics, has really attempted to make economics as a positive-empirical science. The science starts and finishes in empirical datos and eliminates theological and speculative explanations. Realityultimate reality, is the appearance 'orempirical reality. Keyword: philosophy of Economic, Admn